(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Agriculture is the backbone of Indian economy. It is the bedrock and foundation of all efforts for economic development and planning in India. Its growth and success has snow-balling effects over the entire economy. The cooperative movement, which is the largest socio-economic movement in the world, has contributed significantly to the alleviation of poverty, creation of productive 5 employment as well as the enhancement of social integration in the country. The objectives are the Service Attributes, reason for choosing and problems of Primary Agricultural Cooperative Credit Societies. Sample size selected for the study was 80 respondents in the rural areas of Agasteeswarm Taluk in Kanyakumari District. Convenience sampling technique was chose in the selection of the respondents, This study also helpful for the government to identify the attitudes of Primary Agricultural Cooperative Credit Societies‟ customer and their requirements and it is useful to take decision, and make further improvements. This study is about the overall satisfaction level of Primary Agricultural Cooperative Credit Societies‟ respondents.